Follow the eyes: gaze and grammaticality - Hunyadi, Laszlo (Frontiers in Psychology, 2024)
This paper studies the role of eye tracking in detecting grammatical violation in reading tasks. It tests the assumption that encountering syntactic violation has its correspondence in the behavioral patterns associated with gazing. Applying the T-pattern analysis offered by the research environment Theme, it is shown that the observation of grammaticality/agrammaticality in samples of experiments is reflected in the partial correlation of these categories across a number of structural patterns. It is however also shown that their expected difference in the total duration of focusing is not confirmed. It is suggested that associating eye tracking with an additional sound recording or with linguistic ERP studies could widen the categorial spectrum of identifying grammatical violations.